Unrecognized major aortopulmonary collateral arteries in double outlet right ventricle-ventricular septal defect: A rare case report - Siagian, Sisca Natalia; Panjaitan, Elsa Hedia; Wangsaputra, Vincent Kharisma (Heart Science Journal, 2026)
BACKGROUND: Major aortopulmonary collateral arteries (MAPCAs) are aberrant vessels that typically form to compensate for cyanotic congenital heart disease (CHD) with restricted pulmonary blood flow. This often obscures clinical suspicion of MAPCAs in CHDs associ-ated with pulmonary overcirculation, making it potentially unrecognized. CASE ILLUSTRATION: We report the case of a 5-month-old girl presenting with dyspnea, recurrent respiratory infections, and failure to thrive. Echocardiography revealed double outlet right ventricle (DORV) with ventricular septal defect (VSD) and patent ductus arteriosus (PDA). After initial treatment for heart failure and pneumonia, she underwent pul-monary artery (PA) banding and PDA ligation. Ongoing poor postoperative status prompted a second surgery, where intraventricular tunnel repair failed due to inability to wean from cardiopulmonary bypass. An atrial septectomy and PA band retightening achieved hemodynamic improvement, but the patient remained ventilator-dependent with recurrent pneumonia. Further evaluation with multislice CT and catheterisation uncovered previously undiagnosed MAPCAs supplying the right lung and a hypoplastic right pulmonary artery (RPA), precluding embolisation. Since the MAPCAs and hypoplastic RPA were initially unrecognized, the PA banding procedure inadvertently exacerbated the right lung. CONCLUSION: This case highlights the importance of considering MAPCAs in various CHD morphologies and emphasizes the value of pre-procedural imaging selection to optimize surgical planning and outcomes.